Energy utilization potential of Saravan landfill in Rasht with life cycle assessment approach - Ali Ahmadi Orkomi; Maryam Malekpour (علوم محیطی)
Introduction: In addition to causing pollution, landfills also produce greenhouse gases. One of the best methods to assess landfills' environmental impact is to calculate and compare life cycle assessment (LCA) indicators to determine the relative stability of systems. The purpose of this study was to evaluate the environmental effects and economic implications of different methods of Saravan landfill biogas management in Rasht from 2024 forward to determine the most sustainable method for Saravan landfill gas management. Material and methods: Two scenarios were considered for biogas emission estimation from the landfill. In the first scenario, the landfill will be closed in 2024, and in the second scenario, the landfill will be in operation for another 20 years (until 2044). LandGem software has been applied to estimate the amount of biogas emitted from the landfill and the accuracy of results was assessed by the mass balance technique. The LCA study was conducted for three different control situations, including an uncontrolled base case, flare utilization, and electricity generation using internal combustion engines in openLCA software. Waste transportation, landfilling, and biogas management was considered in the system boundary in the life cycle assessment. The leachate treatment process was not investigated because of its negligible effect on the studied indicators. To estimate the emission rates of wastes to the atmosphere in the life cycle assessment software, the LandGem simulation results, international emission factors, and data in the ELCD v2.3 databases were used. Results and discussion: The results showed that in the first and second scenarios, the total amount of biogas generated in the landfill was over 6,600 and 10,500 Gigagrams, respectively. Also, the relative error of LandGem in predicting the generated methane was almost 3.3%. The extracted gas flow rate in the first and second scenarios from 2024 was about 1500 cubic feet per minute. Two flaring and electricity-generating using the internal combustion engine methods have been proposed for landfill gas management with capital costs of 639,000 and 7,120,000 U.S. dollars, respectively. Their annual costs were 18,000 and 918,000 U.S. dollars, respectively. Examining four environmental indicators in life cycle assessment showed that by applying flaring and electricity-generating using the internal combustion engine, global warming potential (GWP100) was reduced by about 30% compared to the uncontrolled base case. So that, the equivalent carbon dioxide emission was almost 3,245, 2,311 and 2,276 kilograms per Mega grams of input solid waste in the base case, the flaring case and the electricity generation case, respectively. Moreover, the photochemical oxidant formation potential in the base case (0.7-kilogram equivalent ethylene per Megagrams solid waste) was much more than that for the other two cases. Meanwhile, the ozone depletion potential was equal for all three management cases. Conclusion: Given the LCA indicators and economic implications, internal combustion engines have been suggested as the most suitable option for landfill gas management after 2024. It not only reduced about 30% of the global warming potential, but also produced 11,000 megawatt-hours of electricity per year. This is almost equal to the average annual electricity consumption of 5,500 households in Guilan Province or 4,000 households in Rasht County.